Influence of support textural property on CO2 to methane activity of Ni/ SiO2 catalysts - Cherevotan, Arjun; Ray, Bitan; Churipard, Sathyapal R.; Kaur, Komalpreet; Gautam, Ujjal K.; Vinod, Chathakudath P.; Peter, Sebastian C. (Applied Catalysis B-Environmental, 2022)
In this work, we elucidated the role of physicochemical textural properties of inert support on the catalyst ac-tivity by impregnating Ni on ordered mesoporous silica (SBA-15 and MCM-41) and non-mesoporous silica (nMPS). The catalyst Ni/SBA-15 exhibited the best CO2 conversion (83%) and product selectivity (99.9 %) followed by Ni/MCM-41 and the least by Ni/nMPS. The difference in the nature of the catalyst, degree of nanoparticle distribution and nanoparticle encapsulation by different silica support were studied by N2 adsorption-desorption and X-ray photoelectron spectroscopy (XPS) experiments. The Operando Diffused Reflec-tance Infrared Fourier Transform Spectroscopy were used to understand the variance in reaction pathway which is accredited to the textural properties of the support. The SBA-15 supported Ni catalyst followed dissociative CO pathway while MCM-41 and nMPS reacted through associative formate mechanism as major pathway. These findings provide a novel perspective on CO2 hydrogenation over Ni-silica, allowing us to tune both activity and selectivity.
Keywords: CO2 methanation; DRIFTS; Mesoporous silica support; Textural properties

Strain-enhanced phase transformation of iron oxide for higher alcohol production from CO2 - Goud, Devender; Churipard, Sathyapal R.; Bagchi, Debabrata; Singh, Ashutosh Kumar; Riyaz, Mohd; Vinod, C. P.; Peter, Sebastian C. (ACS Catalysis, 2022)
Conversion of CO2 to higher alcohols (HAs) and higher hydrocarbons (HCs) has a greater advantage compared to C1 products because of their high energy density and wide range of applications in daily life. Despite the immense potential of these chemicals, not much of scientific research has been focused on the conversion of CO2 to HAs. In the present work, we have introduced the concept of strain in designing the material to enhance the CO(2 )to HA performance. We introduced strain in a traditional iron-based catalyst, Fe2O3, by the introduction of indium (In), which facilitates the selective conversion of CO2 to HA. An optimum strain favored a 36.7% CO2 conversion with a 42% HA selectivity, and a record yield of 15.42%. The strain has been tuned further with the introduction of K as a promoter. The introduced strain upon In substitution and K promotion favored the conversion of CO2, which is mapped by powder X-ray diffraction, X-ray photoelectron spectroscopy, and X-ray absorption spectroscopy. Further, the change in the mechanism upon In incorporation and K promotion has been probed by in situ diffuse reflectance infrared fourier transform spectroscopy, and it is found that the OCHx intermediate, which produces HAs, is more prominent upon In substitution, which favored the enhancement of HA production compared to that of pristine Fe2O3.
Keywords: CO2 to HA; Fischer-Tropsch synthesis (FTS); Phase transformation; reverse water gas shift (RWGS) reaction; strain

Tuning the hybridization and charge polarization in metal nanoparticles dispersed over Schiff base functionalized SBA-15 enhances CO2 capture and conversion to formic acid - Cherevotan, Arjun; Ray, Bitan; Yadav, Anish; Bagchi, Debabrata; Singh, Ashutosh Kumar; Riyaz, Mohd; Churipard, Sathyapal R.; Naral, Vinay; Kaur, Komalpreet; Gautam, Ujjal K.; Vinod, Chathakudath P.; Peter, Sebastian C. (Journal of Materials Chemistry A, 2022)
Different Schiff base functionalized SBA-15 materials were synthesized through condensation reactions between 3-aminopropyltriethoxysilane (APTES) and different aldehydes (glutaraldehyde and butyraldehyde) over a mesoporous silica, SBA-15 (APTES-GLU/SBA-15 and APTES-BUT/SBA-15). Both static and dynamic experiments have been used for testing the CO2 capture efficiency of these materials. The hybridization of the N atom in APTES has been tuned from sp(3) to sp(2) upon condensation facilitating optimum CO2 capture in the direct synthesis of APTES-GLU/SBA-15. The undesirable oxides of nitrogen have been removed during the synthesis process to improve the CO2 capture efficiency. These materials were employed as supports for Pd-Ag and Pd-Ni bimetallic systems for the selective conversion of the captured CO2 to formic acid (FA) in 0.5 M KHCO3 solution. The Pd-Ni catalyst system exhibited enhanced CO2 to FA conversion activity compared to other heterogeneous systems, which is similar to 4 times better than that of the Pd-Ag system in this study. The X-ray absorption studies over the catalyst material confirmed that the relatively electron-deficient Ni in Pd-Ni compared to Ag in Pd-Ag favoured higher charge polarization between the metals in the Pd-Ni system enhancing the CO2 to FA conversion. The experimental observations are well supported by the DFT calculations.